2001
DOI: 10.1038/sj.ejhg.5200575
|View full text |Cite
|
Sign up to set email alerts
|

Major decrease in the incidence of trisomy 21 at birth in south Belgium: mass impact of triple test?

Abstract: In South Belgium (Wallonia), the 'triple test' was introduced in 1990-1991, and is nowadays a widely accepted screening method for assessment of trisomy 21 risk in pregnancy. The 'triple test' is not regulated and can be freely performed by any biomedical lab, making epidemiological data unavailable. By contrast, cytogenetic investigations are limited to a few genetic centres, and accurate statistics can be easily built from their files. During the period 1984-1989, a total of 244 trisomy 21 (1/876 pregnancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…The recent introduction of prenatal diagnoses, such as triplemarker tests and amniocentesis, has dramatically reduced the live birth prevalence of Down syndrome (DS) in many Western countries [Bishop et al, 1997;Cheffins et al, 2000;Verloes et al, 2001;Egan et al, 2004]. In contrast, an increase in live birth prevalence of this syndrome has been reported in Japan [Hoshi et al, 1999;Seto et al, 2003].…”
Section: Introductionmentioning
confidence: 94%
“…The recent introduction of prenatal diagnoses, such as triplemarker tests and amniocentesis, has dramatically reduced the live birth prevalence of Down syndrome (DS) in many Western countries [Bishop et al, 1997;Cheffins et al, 2000;Verloes et al, 2001;Egan et al, 2004]. In contrast, an increase in live birth prevalence of this syndrome has been reported in Japan [Hoshi et al, 1999;Seto et al, 2003].…”
Section: Introductionmentioning
confidence: 94%
“…Improved detection methods including serum screening (maternal serum a-fetoprotein, estriol, and human chorionic gonadotropin) and fetal ultrasound may increase prenatal ascertainment. It has been conclusively shown that increasing maternal age strongly correlates with the incidence of DS (Verloes et al 2001;Forrester and Merz 2002;Bell et al 2003;Khoshnood et al 2004). Trisomy 21 is the most frequently viable autosomal aneuploidy at birth.…”
Section: Own Syndrome (Ds) Is Caused By Trisomy 21 Andmentioning
confidence: 99%
“…The incidence of DS is 1 in 800-1000 live births; the total prevalence of DS (number of affected cases in live births, stillbirths, and terminations) appears to be steady or rising (Leonard et al 2000;Verloes et al 2001;Forrester and Merz 2002;Bell et al 2003;Roizen and Patterson 2003;Khoshnood et al 2004). Improved detection methods including serum screening (maternal serum a-fetoprotein, estriol, and human chorionic gonadotropin) and fetal ultrasound may increase prenatal ascertainment.…”
Section: Own Syndrome (Ds) Is Caused By Trisomy 21 Andmentioning
confidence: 99%
“…The most frequently used approach is first-trimester screening (FTS), which combines nuchal translucency (NT) ultrasound measurement and maternal serum testing to assess the levels of human chorionic gonadotropin (hCG) and pregnancyassociated plasma protein A in combination with age and medical history [1,2]. The triple test (hCG, alpha-fetoprotein, and unconjugated estriol) is used to screen women presenting in the second trimester [3].…”
Section: Introductionmentioning
confidence: 99%